Pendampingan Akuntansi Badan Usaha Milik Desa di Kecamatan Srengat, Blitar, Jawa Timur - Iqbal, Syaiful - (LPPM Universitas Timor, 2024)
This activity emphasizes the ability to record business transactions and prepare financial reports. The location for implementing PkM is in Dermojayan Village, Srengat District, Blitar Regency, East Java Province, attended by BUMDes personnel throughout the district. The method of this activity includes observing problems faced by BUMDes, reflection, action planning, and program implementation. Program implementation is divided into several stages, namely discussions, workshops, training and mentoring, closing and evaluation of activities. Training and mentoring is carried out in the form of providing a set of cases regarding technical calculations of cost of goods manufactured, cost of goods sold, accounting records and preparation of financial reports. As a result, after undergoing PkM activities, participants felt they had gained enlightenment in the form of accounting knowledge and skills in administering all BUMDes business activities. This perception was obtained from the results of the PkM program evaluation carried out at the end of the activity using the google-form-survey evaluation technique which was filled in by 13 BUMDes personnel. Overall, the service activities have succeeded in overcoming the problems faced by BUMDes personnel and succeeded in achieving its goal, namely providing and improving knowledge and accounting skills for BUMDes personnel.